Influência da solidificação direcional nas propriedades mecânicas de uma liga Cu-Al-Be-Nb-Ni com memória de forma - Tiburtino, Gabrielly de Lucena (2019)
There are some years, the alloyes with Effect Memory of form (EMF) has been roughly studied, since, the materials with such properties, present a wide band of possible applications, due to high capacity of recuperation of the its pre-established geometry, after of being exposed to a thermal cycle determined, being thus qualified as unconventional functional materials. In the logic, the present study objective to analyze the thermomechanical properties of the alloy with effect memory of form of nominal composition: Cu-11,8%Al-0,58%Be-0,5Nb-0,27Ni 9% in weight), through of tests of ultra- microhardness in the angles of 0º, 30º, 60º e 90º using as reference the direction of solidification of the columnar grain, in order to get anisotropic knowledges of this alloy. Facing this, it understands that the alloys with effect memory of form have a large comercial attraction, because it treats of a material that in the practice, absorbs and cushions energy. In this perspective, the studied accomplished it is justified by research of a technological path different for the elaboration of the alloy with effect memory of form Cu-AlBe-Nb-Ni, with the pretension of improving the thermomechanical properties of this alloy, being able thus, to increase the field of application. As theoretical targeting, it was taken as base, authors that developed researches in the area and dedicate the studies about of the our object of study. This citing, should be emphasize that the alloy was fused, homogenized during 12h to 850ºC and machined via electroerosion to wire. Posteriorly, the proof bodies were temperate in water to room temperature, and in followed these were analyzed via optical microscopy, scanning differential calorimetric analysis (DSC) and instrumented indentation. From of the accomplished tests, it became possible to observe that, in fuction of the solidification direction, the Cu-Al-Be-Nb-Ni alloy presented a anisotropic behavior for their mechanical properties. It verified yet, a relevant distiction of behaviors of the superelasticity and of the remaining depth of the alloy. The tests yet allowed us to realize that the behavior of the modulus of elasticity, in relation to solidification direction, it is similar to presented by superlasticity. Regarding to application of the load and solidification direction, it was verified the increase and decrease of the hardness DHV-1 when angles varies in determined intervals. Posteriorly, the tests denounced that with the increase of the indentation speed and number of cycles, the superlaticity and the remaining depth pass by some changes. Lastly, it was observed that, as measure that the applied load increaase, the remaining depth plays a similar reaction. And that, concerning superlasticiy, the tests provided a specific perception of this property.